Unmet Needs of Healthcare Services and Associated Factors among a Cohort of Ghanaian Adults: A Nationally Stratified Cross-Sectional Study Design. (June 2021) - Yamson, Phaedra; Tetteh, John; DeGraft-Amoah, Daniel; Quansah, Henry; Mensah, George; Biritwum, Richard; Yawson, Alfred Edwin
We estimated the prevalence of unmet needs of healthcare services (UNHS) and its associated factors among a cohort of older Ghanaian adults. World Health Organization (WHO) Study on Global AGEing and Adult Health for Ghana was used with a total of 4735 participants. Logistics regression analysis was performed using Stata 16 to assess associated factors. The overall UNHS was 3.7% (95% CI = 2.7-4.8) and the prevalence was significantly high amongst older adults aged 60 to 69 years (5.9%). Could not afford the healthcare (56.4%) was the main contender for UNHS. UNHS was influenced by; those aged 60 to 69 years [OR (95% CI) = 1.86 (1.19-2.91)]; no formal educational [aOR (95% CI) = 4.71 (1.27-17.38)], and no NHIS [OR (95% CI) = 1.78 (1.03-3.09)]. Participants needed care for joint pain (25.4%), and communicable diseases (19.1%). The inability to access healthcare was relatively higher for older adults more advanced in age, with low education, and for those without health insurance. Health system strengthening including financial protection by expanding the National Health Insurance Scheme to all Ghanaians in line with Ghana's Universal Health Coverage Roadmap would reduce the unmet healthcare needs of older adults.